Dissecting the genius behind the white lab coat constructing the images of Filipino scientists in films and biographies - Montemayor, Garry Jay S. 1983- (College of Mass Communication, University of the Philippines Diliman, 2013)
"Guided by Barthes' Visual Semiotics, and Adoni and Mane's Social Construction of Reality in the Media theory, a textual analysis of eight Filipino films produced between 1970 and 2009 and six biographical books of filipino scientists published from 1975 to 2007, was done ti surface how films and biographies portray and describe scientists. A Draw-a-Scientist Test and a Focus Group Discussion with seven students were administered to demonstrate how both sets of portrayals construct their image of scientists. films portray scientists as either a/an evil expert, a mad intellectual, ahelpless victim, a hermit prodigy, a foolish professor, a well-rounded genius or a heroic creator. Scientists in the biographies are described as a/an poor kid, a dreamer, a disciplined youngster, an achiever, an accidental scientist, an excellent apprentice, a dedicated worker, a strict educator, a well-rounded researcher, a prolific thinker, an inspiring mentor, and a nurturing family man/woman. The FGD participants' image of scientists include evil and mad, crazy and absent-minded, boring hermits, hardworking and disciplined and inspiring heroes. The study argues that the audiences' subjective images of scientists come from the interaction of meanings constructed both from the scientists' symbolic portrayal in films and objective descriptions in biographies."